The Key Success Factors in Marketing Strategy: A Case Study of a Global Food and Beverage Company - Kia Hui Gan; Hui Ling Lim; Wem Ney Chung; Li Yan Chow; Hui Sin Chua; Zhengyang Dai; Wei Ting Diong; A.J Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Effective marketing strategies play a crucial role in building strong brand equity, and Nestlé has consistently leveraged quality perception, distribution intensity, and advertising to maintain its competitive position in the food and beverage industry. The objective of this research is to examine how Nestlé’s marketing strategies, particularly quality perception, distribution intensity, and advertising, influence brand equity in the competitive food and beverage sector. Additionally, this study aims to investigate the mediating role of brand awareness in strengthening the relationship between these marketing factors and brand equity. A questionnaire was distributed to 200 randomly selected respondents through Google Forms to gain insight into consumer perception. The quantitative methodology was used to analyze the data that had been collected. The results indicate that brand awareness plays a significant role in shaping brand equity, acting as a mediator between key marketing factors and brand perception. Quality perception, distribution intensity, and advertising positively influence both brand awareness and brand equity, confirming their importance in brand development. While brand awareness was found to mediate the relationship between distribution intensity, advertising, and brand equity, it did not significantly mediate the link between quality perception and brand equity. The overall model demonstrates strong explanatory power, highlighting the effectiveness of marketing strategies in strengthening brand equity.